Five new species of Rohrthrips (Thysanoptera: Rohrthripidae) from Burmese amber, and the evolution of Tubulifera wings - Ulitzka, Manfred R. (Zootaxa, 2019)
Rohrthripidae is a family of fossil thrips in the thysanopteran suborder Tubulifera. It includes a single genus, Rohrthrips, of which two species are previously known. Despite typical tubuliferan features, these thrips also show some terebrantian character states, particularly in the wings and antennae, and these are here interpreted as plesiomorphic. Five new species of these ancestral thrips are described from Burmese Cenomanian amber: Rohrthrips breviceps sp. n., Rohrthrips jiewenae sp. n., Rohrthrips maryae sp. n., Rohrthrips patrickmuelleri sp. n. and Rohrthrips schizovenatus sp. n.. Structures on the wings support the conclusion that the wings of Tubulifera are homologous with those of Terebrantia. Syninclusions in the amber fragments provide evidence of the diet and habitats of these ancestral thrips.